Low incidence of significant hydrogel spacer rectal wall infiltration: results from an experienced high-volume center - Woo, Sungmin; Becker, Anton S.; Katz, Aaron E.; Tong, Angela; Vargas, Hebert A.; Byun, David J.; Lischalk, Jonathan W.; Haas, Jonathan A.; Zelefsky, Michael J. (Frontiers in Oncology, 2025)
ObjectivesTo evaluate the incidence and degree of rectal wall infiltration (RWI) of spacer gel used during prostate radiotherapy among two practitioners experienced in using rectal spacers.Materials and methodsConsecutive patients with prostate cancer who received prostate radiotherapy after hydrogel rectal spacer insertion in August 2023–August 2024 by two experienced practitioners were retrospectively included. Post-implant magnetic resonance imaging examinations were evaluated by two radiologists for RWI: 0 (no abnormality), 1 (rectal wall edema), 2 (superficial RWI), and 3 (deep RWI). Scores 2–3 were considered positive for RWI and their location and degree of RWI (radial, longitudinal, and circumferential) were also categorized. Inter-reader agreement was assessed with Cohen’s Kappa.Results215 men were included. Agreement was substantial between the radiologists for RWI scores (Kappa, 0.697; 95% confidence interval, 0.594-0.800). RWI scores were 0 in 80.5% (173/215), 1 in 7.9% (17/215), 2 in 10.7% (23/215), and, 3 in 0.9% (2/215) of the men. Altogether, RWI was present (scores 2–3) in 11.6% (25/215), most commonly in the mid-gland and apex with median radial, longitudinal, and circumferential involvement of 3.2 mm, 8.6 mm, and 11.5%. None of these patients demonstrated any significant rectal toxicity.ConclusionRWI was very uncommon for experienced practitioners. The degree of RWI was focal and not associated with increased complications.